Massive depletion of bovine leukemia virus proviral clones located in genomic transcriptionally active sites during primary infection - Gillet, Nicolas A. (2013)
Deltaretroviruses such as human T-lymphotropic virus type 1 (HTLV-1) and bovine leukemia virus (BLV) induce a persistent infection that remains generally asymptomatic but can also lead to leukemia or lymphoma. These viruses replicate by infecting new lymphocytes (i.e. the infectious cycle) or via clonal expansion of the infected cells (mitotic cycle). The relative importance of these two cycles in viral replication varies during infection. The majority of infected clones are created early before the onset of an efficient immune response. Later on, the main replication route is mitotic expansion of pre-existing infected clones. Due to the paucity of available samples and for ethical reasons, only scarce data is available on early infection by HTLV-1. Therefore, we addressed this question in a comparative BLV model. We used high-throughput sequencing to map and quantify the insertion sites of the provirus in order to monitor the clonality of the BLV-infected cells population (i.e. the number of distinct clones and abundance of each clone). We found that BLV propagation shifts from cell neoinfection to clonal proliferation in about 2 months from inoculation. Initially, BLV proviral integration significantly favors transcribed regions of the genome. Negative selection then eliminates 97% of the clones detected at seroconversion and disfavors BLV-infected cells carrying a provirus located close to a promoter or a gene. Nevertheless, among the surviving proviruses, clone abundance positively correlates with proximity of the provirus to a transcribed region. Two opposite forces thus operate during primary infection and dictate the fate of long term clonal composition: (1) initial integration inside genes or promoters and (2) host negative selection disfavoring proviruses located next to transcribed regions. The result of this initial response will contribute to the proviral load set point value as clonal abundance will benefit from carrying a provirus in transcribed regions.